Digital Marketing Communication on Azarine Cosmetic Social Media Accounts with Lee Min Ho as Brand Ambassador - Anisa Nur Andina; Arfina Ayu Lestari; Fahrul Husna Kusuma Arga (Majalah Ilmiah Bijak, 2023)
Facing the brisk advancement of technology in digital marketing communications, brands are currently faced with strengths in terms of promotion. How they choose brand ambassadors who can represent their brand should not be done haphazardly because when the brand cannot represent the brand, what happens is a failure. Azarine Cosmetic chose Lee Min Ho as a brand ambassador who can represent their brand. Marketing that focuses on social media with target consumers which will later produce royal and loyal consumers. This study uses qualitative research to find that digital marketing communications used by Azarine Cosmetic are effective and can reach potential consumers who ultimately make purchases of the products they produce. Digital marketing communications play an important role in conveying the message the brand wants to convey through posts that are uploaded through various platforms.Â